Federico Mihura Seeber, Usura y capitalismo. La doctrina sobre la usura en el desarrollo del capitalismo medieval, Ed. INCIP-UCA, Buenos Aires, 1984, 96 pp - Di Pietro, Alfredo Gustavo (1985)
Fil: Di Pietro, Alfredo Gustavo. Pontificia Universidad Católica Argentina; Argentina